Pendampingan Penyusunan Media Pembelajaran Interaktif Berbasis Permainan Tradisional untuk Meningkatkan Kreativitas Guru Pendidikan Jasmani di Sekolah Dasar - Fadli Zainuddin; Johan Irmansyah; Sri Erny Muliyani; Rindawan Rindawan; Nurdin Nurdin; Tiassari Janjang Suminar; Fitri Nachamory Oemar (Abdibaraya, 2026)
This Community Service activity aims to improve the competence and creativity of elementary school Physical Education, Sports, and Health (PJOK) teachers in developing interactive learning media based on traditional games. The activity was held in the Hall of SDN 1 Jagaraga, Kuripan District, West Lombok Regency, involving 18 elementary school PJOK teachers. The method used was Participatory Learning and Action (PLA) through stages of coordination, pre-test, material delivery, workshop, media development practice, implementation simulation, mentoring, and post-test. The activity evaluation was carried out using pretest and posttest instruments consisting of 20 questions to measure five competency indicators, namely understanding the concept of interactive learning media, utilizing traditional games as learning media, the ability to design media, the ability to implement media in PE lessons, and the ability to evaluate and develop learning media. The results showed an improvement in participants' competencies, indicated by the increase in the average pretest score from 56.39 (fair category) to 86.94 (excellent category), with an average increase of 30.56 points. The summary of the results also showed a change in participants' competency categories, where before the mentoring, 61.1% of participants were in the fair category and 38.9% in the poor category, while after mentoring, 66.7% of participants reached the excellent category and 33.3% were in the good category. Besides improving conceptual understanding, this activity produces interactive learning media products based on traditional games that are ready to be applied in PE classes. Therefore, the mentoring program has proven effective in enhancing teachers' professional competence while encouraging more innovative, context-based learning that also preserves traditional games as part of local wisdom